Brilliant selling - Cassell, Jeremy; Bird, Tom, 1964- (Pearson, 2021)
Jeremy Cassell has worked as a freelance trainer for 12 years. Before that he was National Training Manager for L’Oreal and National Sales Training Manager for Walker’s, part of Pepsi. Before entering the business world, he gained experience in teaching English and history. He has worked as a TEFL teacher and is an NLP Master Practitioner and trainer. Tom Bird's business career stretches over 20 years and spans sales and sales management as well as personal development and performance improvement. He is a director of RTP and has been involved professionally in developing people to realise more of their potential since 2000. To supplement his business experience Tom qualified as a Master Practitioner of NLP (the study of modelling success) and achieved a Post Graduate Diploma in Coaching and Development.